Pentingnya Pendidikan Islam bagi Pesera Didik di Abad Ke-21 - Saidur Ridlo (LP3M STITNU AL HIKMAH MOJOKERTO, 2020)
The development of education is currently increasingly complex and education currently has an important role for students. This development will affect Islamic education, especially for students in the 21st century. Advances in technology, integration of technology will have an impact on the modernization of Islamic education which will be implemented according to the needs of the times. This study aims to determine the importance of Islamic education in the 21st century as well as to provide solutions to the problems that occur. The research method used in this research is based on literature studies using descriptive-analytic research type. The importance of Islamic education for students is deemed necessary to get attention at this time to get answers to the goals to be achieved so that it will create superior and highly competitive students according to creating creative and innovative characters in developments in the 21st century.